Sintesis ZSM-5 dari coal fly ash (CFA) dengan sumber silika penambah yang berasal dari abu sekam padi: pengaruh rasio SiO2/Al2O3 terhadap kristalinitas produk - Azlia Metta; Simparmin Br Ginting; Hens Saputra (Jurnal Rekayasa Proses, 2014)
Coal Fly Ash and rice husk ash can be utilized by converting it into ZSM-5 synthetic zeolite. One of the influencing factors of ZSM-5 synthetis is ratio of SiO2/Al2O3. Synthesis of ZSM-5 was carried out in an autoclave at a temperature of 180°C with a variation of the ratio of SiO2/Al2O3, namely 20, 30, 40, 50 and 60 mol/mol during 24 hour crystallization using TPABr template. Characterization of ZSM-5 was conducted using X-ray Diffraction, Scanning Electron Microscopy, Adsorption-Desorption Analysis of Nitrogen and Acidity. The results showed that the ZSM-5 was formed in all the variations of SiO2/Al2O3 ratios with the highest percent crystallinity of 52.83%, at the ratio of 50 mol/mol. All products are still in accompany with the formation of side products such as Analsime and Silica Oxide. The ZSM-5 crystal product was in hexagonal shape. Results from Adsorption-Desorption Analysis of Nitrogen indicated that all products were mesoporous materials.